Implant Aesthetics : Keys to Diagnosis and Treatment - Karateew, Edward Dwayne (Springer International Publishing : Imprint: Springer, 2017)
This book, written by acknowledged experts with international reputations, provides clinicians with detailed guidelines on the nature of the ideal anterior dental implant and, more importantly, how the desired aesthetic outcome is to be achieved. It reflects the incredible paradigm shift that has taken place within implant dentistry during the past 5 years, with recognition of the importance of a 'crown down' approach to diagnosis, planning, and treatment, especially in the anterior zone. In order to ensure reproducibility and predictability of treatment outcomes, the fabrication of an aesthetic dental implant must follow a complex algorithm, which is reviewed in a stepwise approach. Sections are devoted to evaluation of the aesthetic implant patient, immediate implant placement, staged implant placement, and restoration. Readers will come to appreciate how the final emergence profile of the definitive restoration reflects the complex interplay of components below the visible smile zone. Helpful flow charts are included that will assist in optimal performance of the described procedures.